Paradox of voting: peril of the vetoing to the perpetual peace - Ibrahimov, Vugar (Vilnius University Open Series, 2023)
The permanent members of the Security Council of the United Nations possess veto power which was vested to them by the Charter of the United Nations to maintain global peace and security. As many, as well as recent events (Russia’s illegal aggression towards Ukraine in 2022) exhibit, in certain circumstances casting veto power, poses some perils to the global peace, per se, and they are twofold. First, all permanent members can exercise this power, according to their will, to block any resolution of the Security Council, including those that deplore their own illegal and illegit actions. The second challenge is the amendment of the UN Charter. The present wording of the UN Charter makes amending the Charter paradoxically onerous, if not impossible (by giving huge power to the permanent members again). Consequently, this situation has long triggered and urged politicians and legal scholars to explore possible solutions. This article will humbly contemplate the issue and explore the suggestions for the reinvigoration of the existing instruments to resolve the current legal and political quagmire.